Investigation of the inner structures around HD 169142 with VLT/SPHERE - Ligi, Roxanne; Pohl, Adriana (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We present observations of the Herbig Ae star HD 169142 with the VLT/SPHERE instruments InfraRed Dual-band Imager and Spectrograph (IRDIS) (K1K2 and
In original form 2017 March 2
Gesehen am 20.02.2020